The ethics of talent management. (21st November 2012) - Swailes, Stephen
Abstract : Organisational approaches to talent management are often concerned with the ways that a small proportion of relatively high‐performing employees are identified and managed in relation to the majority. Despite a growing literature on talent management, no papers have provided any guidance on how to evaluate it from an ethical standpoint. After considering what is meant by talent, this paper considers the ethical issues that arise from the operation of talent management programmes. These considerations are then used to create a framework that has the potential to influence the practical design of talent programmes and which may focus further debate into the ethics of talent management.